EFFECT OF ADDING RESVERATROL TO SOYBEAN-LECITHIN EXTENDER ON SOME SEMEN ATTRIBUTES OF BUFFALO BULLS - A. M. Alhelal,; T. A. Abdulkareem, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to explain the effect of adding different resveratrol (Res) concentrations to soybean-lecithin extender on some post-cryopreserved (PC) semen characteristics of the Iraqi buffalo bulls for different preservation periods. Eight mature bulls were used, and polled semen was equally divided into four groups within one trial. Three Res concentrations (100, 150, and 200 μM) were added to the soybean-lecithin extender, and comparisons in the response were made with the control group (soybean-lecithin extender, Res-0). The differences among groups in sperm cell individual motility percentages at different preservation periods lacked significance. Greater (P≤0.01) sperm acrosome integrity percentage was noticed for the Res-150 group compared with the C and Res-200 groups at cooling, 48 hrs., and 2 months PC. Lesser (P≤0.01) malondialdehyde concentrations and sperm DNA damage percentage were observed for the Res-150 group as compared with the other groups, 2 months PC. Higher (P≤0.01) total antioxidant activity was shown in Res-150 and Res-200 groups as compared with the control and Res-100 groups, 2 months PC. In conclusion, adding Res to the soybean-lecithin extender enhanced some of the PC semen characteristics of Iraqi buffalo bulls at different preservation periods.